A brief bibliometric statistical analysis of gender issues in tourism using the Scopus database (ҚазҰУ Хабаршысы. География сериясы, 2025)
Various publications on gender issues in tourism were collected and selected using one of the most popular databases, Scopus. The research documents are publications from the last 2 decades (between 2004 and 2023). The Scopus analyzer is used to obtain some analysis results of scientific publications, such as year, source, country, etc. VOSviewer version 1.6.17 is used to analyze different units such as co-authorship and co-occurrences. Statistical analysis and network analysis indicates that the highest number of documents were published in 2022 and 2023, with Spain having the highest number of publications. The results also show that in the first 10 years, the number of publications was very small, and the growth was uneven, but in the following 10 years, the number of published articles gradually increased in general, especially from 2021, the number of publications increased significantly. Researchers from Spain, the UK, the USA and Australia publish more than 50% of all published documents worldwide, ahead of 59 other countries and territories. In addition, the top 10 most productive institutions in terms of publications are from the above-mentioned countries. It can be said that the study of gender in tourism was initiated by scholars from democratic English-speaking countries and some Western countries, and mass interest only arose after the end of the COVID-19 pandemic. Network analysis of various parameters shows that there is much room for further research on women's leadership, empowerment and employment.